Foreword - (reviewers’ view) - Sadri, Sorab (Journal of Economic Development, Environment and People, 2013)
It is indeed a singular honor to be asked to write this Foreword for a prestigious journal like JEDEP that has now come out with its fifth issue. I would like to share a thought that came to me as I was reading the abstracts. When you are presented with a bouquet of flowers all of the same hue and color it is beautiful. But when the flowers are in various colors but yet of the same biological genre this beauty is enhanced. That is true of this issue of the journal and the contribution of the authors as well. To begin with, for a person who has been looking into organizational excellence and business sustainability for the past two decades, this cluster of essays made delightful reading...